Brazeability, Microstructure, and Joint Characteristics of ZrO2/Ti-6Al-4V Brazed by Ag-Cu-Ti Filler Reinforced with Cerium Oxide Nanoparticles - Ashutosh Sharma; Byungmin Ahn (Advances in Materials Science and Engineering)
In this work, we have attempted to develop the Ag-Cu-Ti filler for bonding ZrO2 to Ti-6Al-4V. The CeO2 nanoparticles were reinforced in the eutectic Ag-Cu-Ti filler via mechanical mixing and melting route. Furthermore, the brazeability, microstructure, and mechanical behavior, as well as brazing performance of the ZrO2/Ti-6Al-4V joints, were assessed. The wettability of the Ag-Cu-Ti matrix was increased from 89 to 98% on Ti-6Al-4V and from 83 to 89% on the ZrO2 substrate after the addition of 0.05% CeO2. Also, there was a depression in the melting point of the composite fillers up to 3°C. The microstructure consists of Cu- and Ag-rich phases and Cu-Ti intermetallic compounds (IMCs). The joint shear strength was improved with the addition of CeO2 up to 0.05 wt.% in the matrix. It was inferred that, for an excellent brazing performance of the ZrO2/Ti-6Al-4V joint, the optimum amount of CeO2 should be 0.05 wt.% in the Ag-Cu-Ti matrix.